2008
DOI: 10.1111/j.1939-1676.2008.0062.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Filtration Rate in Dogs with Leishmaniasis and Chronic Kidney Disease

Abstract: Background: Glomerular filtration rate (GFR) measurement is an indicator of kidney function. However, its usefulness in dogs at early stages of spontaneous chronic kidney disease (CKD) of glomerular origin, where routine laboratory techniques are not sufficiently sensitive, remains unproved. Hypothesis: That GFR is reduced in proteinuric nonazotemic or mildly azotemic dogs with CKD secondary to leishmaniasis. Animals: Twenty‐six dogs with CKD secondary to leishmaniasis and 10 healthy dogs (control group). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 31 publications
2
31
1
4
Order By: Relevance
“…Unfortunately, their study did not provide a histopathological assessment of the kidneys, so that any association between hypertension and renal injuries could be anticipated. Another study by Cortadellas et al (2008) investigating 26 dogs with visceral leishmaniasis and microalbuminuria, an early surrogate of glomerular lesion, documented 34.7% (9/26) of hypertension, which is also similar to our results, but contrasted with a very recent study, in which only 8.8% of Leishmania spp. infected dogs were diagnosed with systemic arterial hypertension, even though an UPC >0.5 were identified in 83.3% of them (Braga et al 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unfortunately, their study did not provide a histopathological assessment of the kidneys, so that any association between hypertension and renal injuries could be anticipated. Another study by Cortadellas et al (2008) investigating 26 dogs with visceral leishmaniasis and microalbuminuria, an early surrogate of glomerular lesion, documented 34.7% (9/26) of hypertension, which is also similar to our results, but contrasted with a very recent study, in which only 8.8% of Leishmania spp. infected dogs were diagnosed with systemic arterial hypertension, even though an UPC >0.5 were identified in 83.3% of them (Braga et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Although the studies by Cortadellas et al (2006) and Cortadellas et al (2008) classified the animals as hypertensive only when documenting either a SAP ≥180mmHg or a SAP between 150 and 179mmHg with overt clinical manifestations attributable to systemic hypertension, and Braga et al (2015) considered a SAP cut-off of ≥160mmHg, the consensus statement on systemic hypertension in small animals defined such condition as a sustained increase in blood pressure, even though target organ lesions, including the reduction in glomerular filtration rate, ocular lesions, and hypertensive encephalopathy, are only likely to occur when a SAP >160 mmHg is identified (Brown et al 2007). Actually, some dogs recruited for this investigation were classified as hypertensive because the SAP was greater than the normal reference range proposed by two large systematic investigations (Bodey & Michell 1992, Mishina et al 1997, but the majority of these animals were undoubtedly at minimal to mild risk of target organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…8,29,116,153 This proteinuric nephropathy progressively leads to excretory dysfunction or sometimes to decreased or increased glomerular filtration rate and to systemic hypertension that can establish a vicious cycle, thus amplifying the underlying glomerular pathology. 25,26 Ocular disease is quite common in CanL and can be the only or the main clinical manifestation in 3.7% to 16% of the affected dogs. 22,73,93,110 Ocular pathology in leishmanial dogs has revealed that the granulomatous and lymphoplasmacytic inflammatory infiltration of ocular tissues involves, in order of frequency, the conjunctiva, limbus, ciliary body, iris, cornea, sclera and iridocorneal angle, choroid, and the optic nerve sheath.…”
Section: General Pathomechanismsmentioning
confidence: 99%
“…Jong-Hyun YOO 1) , Chul PARK 2) , Dong-In JUNG 3) , Chae-Young LIM 1) , Byeong-Teck KANG 1) , Jung-Hyun KIM 1) , Jung-Won PARK 4) , Jae-Hoon KIM 5) and Hee-Myung PARK 1) Recently, the potential for renal repair by using stem cells has been elucidated for various renal diseases [6,8,13]. Among stem cell sources, bone-marrow stem-cells (mesenchymal stromal cells; MSCs) have attracted interest due to their accessibility and great degree of plasticity [13].…”
Section: In Vivo Cell Tracking Of Canine Allogenic Mesenchymal Stem Cmentioning
confidence: 99%
“…Plasma creatinine concentrations (mg/dl) were measured by use of an autoanalyzer (Cobas c III, Roche Diagnostics). The calculations of GFR were performed by use of a computer software program (Creatinine clearance calculator, Royal Canine, St. Charles County, MO, U.S.A.) with previously described protocol [2,19]. For histological evaluations, renal tissue sections were stained with hematoxylin-eosin.…”
Section: In Vivo Cell Tracking Of Canine Allogenic Mesenchymal Stem Cmentioning
confidence: 99%